392 The uptake and impact of HPV vaccination on cervical cancer incidence 10 years after FDA approval in United States. (13th November 2020) - Liao, C; Furey, K; Richardson, M; Tran, K; Mann, AK; Maxwell, L; Hamilton, CA; Tian, C; Darcy, KM; Kapp, DS; Chan, JK
Abstract : Objective: To determine incidence of cervical cancer following FDA approval of HPV vaccine in the United States. Methods: HPV vaccination coverage was derived from the National Immunization Survey-Teen (NIS-Teen). Cervical cancer data were derived from the United States Cancer Statistics database for those aged<35 (those eligible for vaccination at 2006 FDA approval, ages 9–26), adjusting for hysterectomy and pregnancy prevalence from the Behavioral Risk Factor Surveillance System. SEER*Stat and Joinpoint regression were used to calculate the incidence (age-standardized rate/100, 000) and average annual percent change (AAPC). Results: As of 2016, 65.1% teens (13–17) initiated HPV vaccination and only 43.3% completed the series. We evaluated those (age 9–26yo) who were age eligible for vaccination in 2006 and followed this group to 2014, 8 years later, to determine the potential decrease in cervical cancer incidence. The 35–39yo who were ineligible for vaccination in 2006 had an incidence of 8.88/100, 000 compared to 7.21/100, 000 in those (30–34yo) who were eligible. Over the study period, the incidence of cervical cancer for those aged 30–34 decreased by 0.9% per year (p<0.001). By race, incidence decreased per year most for Hispanic women (1.4%), followed by White (1.3%) and Black (1.0%, all p<0.001). Conclusion: Although 65.1% initiated the human papillomavirus vaccination, only 43.3% completed the series. Due to low overall vaccination rates, larger studies with longer follow up of vaccinated individuals are warranted to determine the contribution of vaccination on the decrease in cervical cancer incidence.